Endoscopic Endonasal versus Open Repair of Anterior Skull Base CSF Leak, Meningocele, and Encephalocele: A Systematic Review of Outcomes - Komotar, Ricardo J.; Starke, Robert M.; Raper, Daniel M. S.; Anand, Vijay K.; Schwartz, Theodore H. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Repair of anterior skull base cerebrospinal fluid (CSF) leaks, encephaloceles, and meningoceles can prevent meningitis, intracranial abscess, and pneumocephalus. Various surgical techniques have been employed for repair, including open transcranial and transfacial methods. The endoscopic endonasal approach represents a minimal access but equally aggressive alternative. We conducted a systematic review of case series and case reports to assess the role of endoscopy in the management of these lesions.Methods We performed a MEDLINE search of the literature (1950–2010) to identify open and endoscopic surgical series for repair of anterior skull base CSF leaks, encephaloceles, and meningoceles. Comparisons were made for patient and defect characteristics as well as success of repair, morbidity, and outcome.Results Seventy-one studies, involving 1178 patients, were included. There was no significant difference in the rate of successful repair (~90%) between the open and endoscopic cohorts. Compared with open approaches, complications were significantly lower in the endoscopic group, including meningitis (3.9% versus 1.1%, p = 0.034), abscess/wound infection (6.8% versus 0.7%, p < 0.001), and sepsis (3.8% versus 0%, p = 0.003). Perioperative mortality was also lower in the endoscopic group (0%) compared with the open group (1.4%) (p < 0.001).Conclusion Our systematic review supports the endoscopic endonasal approach as a safe and effective alternative for the treatment of anterior skull base defects, which may be preferable in select patients.
Keywords: CSF leak; encephalocele; endoscopic; meningocele; systematic review; skull base